Osteogenic Differentiation Capacity of In Vitro Cultured Human Skeletal Muscle for Expedited Bone Tissue Engineering. (22nd January 2017) - Miao, Chunlei; Zhou, Lulu; Tian, Lufeng; Zhang, Yingjie; Zhang, Wei; Yang, Fanghong; Liu, Tianyi; Tang, Shengjian; Liu, Fangjun
Abstract : Expedited bone tissue engineering employs the biological stimuli to harness the intrinsic regenerative potential of skeletal muscle to trigger the reparative process in situ to improve or replace biological functions. When genetically modified with adenovirus mediated BMP2 gene transfer, muscle biopsies from animals have demonstrated success in regenerating bone within rat bony defects. However, it is uncertain whether the human adult skeletal muscle displays an osteogenic potential in vitro when a suitable biological trigger is applied. In present study, human skeletal muscle cultured in a standard osteogenic medium supplemented with dexamethasone demonstrated significant increase in alkaline phosphatase activity approximately 24-fold over control at 2-week time point. More interestingly, measurement of mRNA levels revealed the dramatic results for osteoblast transcripts of alkaline phosphatase, bone sialoproteins, transcription factor CBFA1, collagen type I, and osteocalcin. Calcified mineral deposits were demonstrated on superficial layers of muscle discs after an extended 8-week osteogenic induction. Taken together, these are the first data supporting human skeletal muscle tissue as a promising potential target for expedited bone regeneration, which of the technologies is a valuable method for tissue repair, being not only effective but also inexpensive and clinically expeditious.